Low-velocity impact behaviour of hemp fibre reinforced bio-based epoxy laminates. (15th April 2016) - Scarponi, Claudio; Sarasini, Fabrizio; Tirillò, Jacopo; Lampani, Luca; Valente, Teodoro; Gaudenzi, Paolo
Abstract: This work addresses the damage resistance and post-impact damage tolerance of hemp fabric reinforced bio-based epoxy composites subjected to low-velocity impact at energies ranging from the barely visible impact damage (BVID) threshold up to perforation. A comparison is also reported with similar composites in terms of thickness and fibre volume fraction but based on a traditional epoxy matrix. The results confirmed the significant toughness of laminates based on a bio-based epoxy matrix and their superior damage tolerance compared to standard hemp-epoxy laminates, thus highlighting their potential use in semi-structural applications due to an improved interfacial adhesion with hemp fibres.